Model Blended learning Pada Pembelajaran Pendidikan Agama Islam Di Sekolah Dasar - Khatipah; Rusyaid; Mutmainna; Mut’mainna, Tasya (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study aims to analyze the implementation of the blended learning model in Islamic Religious Education (PAI) at the elementary school level. The research was conducted at SDIT Al Izzah Sorong during the even semester of the 2020–2021 academic year, when face-to-face learning was still restricted due to the COVID-19 pandemic. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation involving the foundation board, school leaders, teachers, and parents. The findings show that blended learning was applied by combining offline and online instruction with a rotation system in which students were divided into two groups to comply with health protocols. PAI learning was carried out once a week for one lesson hour, covering the stages of planning, implementation, and evaluation in accordance with blended learning principles. Despite its potential to increase student engagement and maintain teacher–student interaction, several challenges emerged. Teachers encountered difficulties in adapting to the new model, developing creative instructional strategies, and supporting students who struggled with the material. Students experienced decreased learning motivation and boredom, while parents faced obstacles such as limited digital literacy, restricted financial resources for internet access or devices, and excessive involvement in completing their children’s assignments. These findings indicate that effective and sustainable blended learning requires enhanced teacher capacity, adequate technological support, and stronger collaboration between schools and parents.